Paul on the Human Vocation Reason Language in Romans and Ancient Philosophical Tradition - Dürr, Simon (Beihefte zur Zeitschrift für die neutestamentliche Wissenschaft, 2021)
This book offers a new explanation for Paul's puzzling use of λογικὴ λατρεία (Rom 12.1). Based on a detailed investigation of ancient philosophical parallels, it argues that Paul here alludes to discourse on the role of human beings in the cosmos, which he sees fulfilled in Christ-followers in particular. It charts the implications of this interpretation for reading Romans and contributes to a possible integration of Paul's theology and ethics.